NS1 antigen testing for the diagnosis of dengue in returned Israeli travelers. Issue 12 (6th January 2014) - Fuchs, Inbal; Bin, Hana; Schlezinger, Sara; Schwartz, Eli
<x xml:space="preserve">Abstract</x> Antigen testing with NS1 provides rapid diagnosis of dengue in endemic regions during the febrile phase of illness before appearance of IgM in serum. This study aimed to determine the diagnostic accuracy of NS1 antigen testing in travelers presenting with febrile illness and serologically confirmed dengue infection, upon return from dengue endemic countries to Israel, a region endemic for West Nile virus (WNV). Cases were sera obtained from febrile returning travelers with positive dengue‐IgM antibodies. Sera of non‐travelers with confirmed WNV disease and sera of returning travelers with confirmed non‐dengue febrile illnesses were used as controls. All sera were tested for NS1 antigen using the Panbio Dengue Early ELISA assay within 21 days of symptoms. Demographic data, travel destination, and interval between disease onset and testing were retrieved from patient files. Fifty‐eight sera from 40 dengue‐infected travelers, 26 sera from 26 WNV‐ infected patients, and 15 sera of returning travelers with non‐dengue febrile illness were tested. Sensitivity of NS1 testing in dengue patients was 87% during the first 3 days of symptoms and declined to about 70% after 12 days. No cases tested positive for NS1 after day 12. Specificity was 92% for the entire testing period. The NS1 Panbio assay is sensitive for the detection of dengue viral infection in returning travelers during the febrile phase of illness, and is highly specific in a region where WNV co‐circulates. J. Med. Virol. 86:2005–2010, 2014. © 2014 Wiley Periodicals, Inc.